A Genetic Toolbox for the New Model Cyanobacterium Cyanothece PCC 7425: A Case Study for the Photosynthetic Production of Limonene - Chenebault, Célia; Diaz-Santos, Encarnación; Kammerscheit, Xavier; Görgen, Sigrid; Ilioaia, Cristian; Streckaite, Simona; Gall, Andrew; Robert, Bruno; Marcon, Elodie; Buisson, David-Alexandre; Benzerara, Karim; Sassi, Jean-François; et al. (Frontiers in Microbiology, 2020)
Cyanobacteria, the largest phylum of prokaryotes, perform oxygenic photosynthesis and are regarded as the ancestors of the plant chloroplast and the purveyors of the oxygen and biomass that shaped the biosphere. Nowadays, cyanobacteria are attracting a growing interest in being able to use solar energy, H2O, CO2 and minerals to produce biotechnologically-interesting chemicals. This often requires the introduction and expression of heterologous genes encoding the enzymes that are not present in natural cyanobacteria. However, only a handful of model strains with a well-established genetic system are being studied so far, leaving the vast biodiversity of cyanobacteria poorly understood and exploited. In this study, we focused on the robust unicellular cyanobacterium Cyanothece PCC 7425 that has many interesting attributes, such as large cell size; capacity to fix atmospheric nitrogen (under anaerobiosis) and to grow not only on nitrate but also on urea (a frequent pollutant) as the sole nitrogen source; capacity to form CO2-sequestrating intracellular calcium carbonate granules and to produce various biotechnologically interesting products. We demonstrate for the first time that RSF1010-derived plasmid vectors can be used for promoter analysis, as well as constitutive or temperature-controlled overproduction of proteins and analysis of their sub-cellular localization in Cyanothece PCC 7425. These findings are important because no gene had been developed for Cyanothece PCC 7425, yet, handicapping its potential to serve as a model host. Furthermore, using this toolbox, we engineered Cyanothece PCC 7425 to produce the high-value terpene, limonene which has applications in biofuels, bioplastics, cosmetics, food and pharmaceutical industries. This is the first report of the engineering of a Cyanothece strain for the production of a chemical and the first demonstration that terpene can be produced by an engineered cyanobacterium growing on urea as the sole nitrogen source.